Needs Analysis of Ethnoscience-Based Digital Teaching Materials for Grade IV Elementary School Students - Nur DS, Yulistina; Hufad, Achmad; Leksono, Suroso Mukti; Dewi, Sinta Maria; Latifatusadiah, Tia (Journal of Educational Analytics, 2024)
Learning that raises local culture to be a subject of science learning can improve students' mastery of science literacy, character, motivation and interest. This study aims to analyze the needs of ethnoscience-based digital teaching materials in elementary schools. This type of research is descriptive qualitative, namely by analyzing needs. This research was conducted in class IV of SDN located in East Karawang District, Karawang Regency. The data collection techniques used were interviews and observations. The results of this study indicate that: 1) Ethnoscience-based digital teaching materials at the school have never been developed; 2) There is a great need for ethnoscience-based digital teaching materials on plant material sources of life on earth; 3) Ethnoscience-based digital teaching materials really need to be developed in learning grade IV science on plant material sources of life on earth.